MENUMBUHKAN KARAKTER SISWA BERBASIS BUDAYA TABE’ DI ERA DIGITAL (Studi Kasus Pada Siswa Madrasah Tsanawiyah Takalar) - Desy Ayu Andhira; Hamriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
his study aims to determine the application of tabe' culture among students of Madrasah Tsanawiyah in Takalar, to determine the application of tabe' culture among students of Madrasah Tsanawiyah in Takalar in the digital era, and to determine the influence of tabe' cultural values and practices on the character formation of Madrasah Tsanawiyah students in Takalar. The method used in this study is a qualitative research method using interviews and observations to collect data. The results of the study show that Madrasah Tsanawiyah students in Takalar still apply and consider tabe' culture as an important culture to be preserved and remain relevant to the times. The application of tabe' culture is classified into two based on its implementation, namely tabe' culture in the form of speech and in the form of actions. The application of tabe' culture is supported by two factors, namely internal factors and external factors. The application of tabe culture in the digital era is also still relevant. Tabe's culture has a very large influence on the formation of student character because it contains the values of sipakatau (not discriminating against everyone), sipakalabbiri’ (mutual respect), and sipakainga’ (reminding each other).